A prospective observational study of how veterinary clinics and their clients utilized a no-credit-check, third-party managed installment financing option to increase access to veterinary care - Cammisa, Heather J.; Hill, Samantha (Frontiers in Veterinary Science, 2025)
The top client barrier to veterinary care is financial. Clients have reported their desire for more payment options, with recent research findings indicating that, with them, pet families could double the amount they could spend on lifesaving care. Research in 2022 reviewed cash and credit challenges that contribute to financial barriers and analyzed one option yet did not have direct engagement with clinics. This current study collected and analyzed data from 16 clinics to identify clinic and client impacts of expanded payment options in veterinary medicine. Clinics added at least one Varidi® payment option disassociated with a credit check of any kind. Clients reported why they used the payment option and the likelihood of alternatives they would have faced in the absence of having the option. Clinics overwhelmingly offered the option that guaranteed payment to the clinic. The average term was 9 months. The majority of those who used the option were existing clients of the clinic who sought sick, injury, surgery, or end-of-life care and received care at clinics offering credit-based financing. More than one in three cases (35.8%) faced a severe break in the human–animal bond (HAB), such as giving up their pet or putting their pet to sleep in the absence of the payment option. Combined with cases where the client was “very likely” to seek a lower cost option elsewhere, provide less care for their pet, or treat their pet on their own, 52% of cases met this risk to the clinic–client–patient relationship (REL), impacting clinic revenue and professional goals.